The Influence of Workload, Personality, Working Period, and Leadership Style on Work Stress and Its Impact on Nurse Burnout at Dr. M.M Dunda Limboto Hospital - Nur Inaya Buo; Sabirin B. Syukur; Rini Asnawati (Universitas Muhammadiyah Palu, 2026)
Nurses are the spearhead of health services that are vulnerable to work stress and burnout due to high job demands, large responsibilities, and long working hours. Burnout can reduce the quality of service and work productivity of nurses. This study aims to analyze the influence of work period, workload, personality, and leadership style on work boredom with work stress as a mediating variable in nurses at Dr. M.M Dunda Limboto Hospital. The research sample amounted to 90 nurses who were taken with a total sampling technique. Data analysis was carried out using Univariate, Bivariate, and Multivariate analysis (path analysis) through the SPSS version 25 program to test the direct and indirect influence between variables. The results showed that there was an influence of work period, personality workload, and leadership style factors with burnout in nurses at Dr. M.M Dunda Limboto Hospital with p. Value (0.000 ? 0.05) while simultaneously the variables of working period, workload, personality, and leadership style had a significant effect on work stress (R² = 0.68). Partially, workload (? = +0.55; p = 0.000) had the strongest positive effect on work stress and working time (? = +0.28; p = 0.004) had a moderate positive effect, while personality (? = ?0.41; p = 0.000) and leadership style (? = ?0.33; p = 0.000) had a significant negative effect. Work stress itself had a significant positive effect on burnout (? = +0.63; p = 0.000), with a value of R² burnout = 0.74. The largest indirect influence on burnout occurred through the workload pathway ? work stress ? burnout (total ? = +0.72). The conclusion of this study shows that workload is the most dominant factor that increases nurse burnout, while a stable personality and supportive leadership style play an important role in reducing work stress and preventing burnout. These findings underscore the importance of workload management and transformational leadership development in an effort to maintain the psychological well-being of nursing staff.